False luminescence of molybdenum disulfide quantum dots from carbon dots. Issue 51 (7th June 2022) - Fu, Xiaolong; Huang, Ju; Zhu, Xiajun; Rong, Jiefeng; Lin, Zhenyu; Dong, Yongqiang; Fu, Fengfu
Abstract : A systematical investigation has been carried out for the first time to prove that there are no luminescent molybdenum disulfide quantum dots. Abstract : For the first time, a systematical investigation has been carried out to verify luminescent molybdenum disulfide quantum dots (MoS2 QDs). We found that the well-reported blue fluorescence of the so-called "MoS2 QDs" is mainly originated from the co-present carbon based dots rather than MoS2 . Furthermore, the band gap of MoS2 is independent of the lateral size, and it is impossible to obtain luminescent MoS2 QDs by reducing the lateral size.